Modification blanching process of potato flour using hydrogen rich water - Gita Indah Budiarti; Lukhi Mulia Shitophyta; Ndaru Okvitarini; Vinna Fajarwaty; Ayu Damayanti (Reaktor, 2020)
The chemical composition of potatoes includes carbohydrates, protein, fiber, vitamins, and minerals. The composition of vitamins and minerals in potatoes is higher than wheat flour. Brownish color in potato flour has reduced consumer's interest, so it needs to be modified to improve the color and physicochemical properties of flour. Researchers are trying to modify the blanching process using hydrogen-rich water. Because hydrogen-rich water has antioxidants that can prevent the browning process (oxidation) potato flour, cheaper, safer, and healthier than chemical compounds. The purpose of this study was to optimize the blanching process for potato flour modification. Variation of the process used is soaking time at 30, 45, 60, 75, and 90 minutes. The optimal results of water content, ash content, reducing sugar content, protein, color, and swelling power were obtained at 75 minutes are 6.7%, 2.68%, 0.26%, 7.1%, 81.17, and 7 g/g. The quality of the modified potato flour met the physicochemical parameters of the flour according to the SNI standard for flour, except ash content. The quality of potato flour produced almost equals as the quality of wheat flour, so it needs to be considered as a substitute for wheat flour and is friendly for diabetics.Keywords: potatoes, modified flour, physicochemical properties, wheat